Saltmarsh Caterpillar, Estigmene acrea (Drury) (Insecta: Lepidoptera: Arctiidae) - John L. Capinera (EDIS)
The saltmarsh caterpillar, Estigmene acrea (Drury), is a native insect found throughout the United States. Its distribution extends to Central America, and in Canada it has damaged crops in Ontario and Quebec. As a pest, it is most common in the southern United States, particularly the southwest. This document is EENY-218, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.